1986
DOI: 10.1159/000199335
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptophan and Cisapride Stimulate Propulsive Jejunal Motility and Transit of Chyme in Dogs

Abstract: We investigated in conscious dogs the effects of intravenously administered 5-hydroxytryptophan (5-HTP) and cisapride on the postprandial jejunal mechanical activity by means of six closely spaced extraluminal strain gauge transducers. Drugs were given after administration of a nutrient meal. 5-HTP was given additionally after the administration of a noncaloric cellulose meal. Computer assistance was used to determine the temporal and spatial relationship of contractions and thereby to evaluate the length of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Our analysis of myoelectrical tracings was designed to detect events that propagated over a distance of at least 10 cm in the jejunum (at a speed ≥ 0.5 cm s –1 ) and at least 15 cm in the colon (at a speed ≥ 0.25 cm s –1 ). These parameters were chosen after a review of the literature, showing that another 5‐HT 4 receptor agonist, cisapride, stimulated propagated motor patterns in the canine and human jejunum with propagation distance and velocity that are similar to those reported in this study 36 –38 . The colonic migrating myoelectrical events observed in this study correspond to the groups of long spike bursts described in the dog colon by Fioramonti et al.…”
Section: Discussionsupporting
confidence: 76%
“…Our analysis of myoelectrical tracings was designed to detect events that propagated over a distance of at least 10 cm in the jejunum (at a speed ≥ 0.5 cm s –1 ) and at least 15 cm in the colon (at a speed ≥ 0.25 cm s –1 ). These parameters were chosen after a review of the literature, showing that another 5‐HT 4 receptor agonist, cisapride, stimulated propagated motor patterns in the canine and human jejunum with propagation distance and velocity that are similar to those reported in this study 36 –38 . The colonic migrating myoelectrical events observed in this study correspond to the groups of long spike bursts described in the dog colon by Fioramonti et al.…”
Section: Discussionsupporting
confidence: 76%
“…There is evidence to suggest that the substituted benzamide cisapride, which has prokinetic properties and stimulates the phasic motor activity of the gastrointestinal tract by potentiating the release of acetylcholine from postganglionic cholinergic nerves (Chey et al ., 1984; Suzuki et al ., 1985; Schemann & Ehrlein, 1986; Fujii et al ., 1988; Strombeck et al ., 1988; Schuurkes & Van Nueten, 1990), may also promote detrusor muscle motility. This action appears to be beneficial in cases of urinary retention caused by several agents and clinical studies have reported successful use of cisapride in the treatment of neuropathic bladder (Ettienne et al ., 1988), in urinary retention following prostatechtomy (Meier et al ., 1996), or even in cases of lazy bladder syndrome (Franceschetti et al ., 1997; Kroll et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Transit studies have shown the propulsive properties of cisapride in the small intestine (7,8) and its effects on fasting and postprandial gastrointestinal motility have been well established (9 -13).…”
mentioning
confidence: 99%